Communication Accommodation of South Sumatra Students in Intercultural Communication at University Muhammadiyah of Surakarta - Rizka Fitriana; Yanti Haryanti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study discusses the communication accommodation process of students from South Sumatra in interacting with the local at Uuniversity Muhammadiyah Surakarta. The background of this study is based on the differences in language, character, and social customs between the Javanese community and students from South Sumatra, which pose challenges in the process of intercultural communication. The purpose of this study is to understand the forms of communication adjustment made by students in facing cultural differences and the strategies used to adapt to a new environment. This study uses a descriptive qualitative approach with six informants who are students from South Sumatra from the 2021-2023 batch. The results show that students experience culture shock at the beginning of their studies due to differences in language and manners. However, through the process of communication accommodation, they began to adjust their speaking style, tone of voice, and social behavior in accordance with Javanese cultural norms (convergence), without losing their original cultural identity (divergence). This adaptation process had a positive effect on their ability to interact, increased social acceptance, and strengthened mutual respect between cultures on campus.